2007
DOI: 10.1089/neu.2006.0196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Rural Trauma System on Traumatic Brain Injuries

Abstract: The response of trauma systems in rural areas is uncertain since distances between injury scenes and trauma care are considerable. Timely arrival at definitive care is critical for persons with traumatic brain injury (TBI) since secondary damage can occur during the hours following injury. We evaluated how the implementation of a trauma system in a predominately rural state affected the triage of TBI patients and their risk for mortality. The Iowa System Trauma Registry Dataset was analyzed, and included patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…This is why calls continue to be made for the establishment, at least, of regional trauma centers in many of these LMIC for the optimal care of the critically head injured [1,11,31] .…”
Section: Outcome Of Hi In Nigeriamentioning
confidence: 99%
“…This is why calls continue to be made for the establishment, at least, of regional trauma centers in many of these LMIC for the optimal care of the critically head injured [1,11,31] .…”
Section: Outcome Of Hi In Nigeriamentioning
confidence: 99%
“…[1][2][3][4][5] Most trauma centers are in urban regions. In a rural state, referral to a major center presents greater obstacles and increased difficulty for injured patients who must travel long distances for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that TBI results in the greatest public health burden in terms of YPLL due to in-hospital death while other neurologic disorders have shown improvements in mortality and YPLL over time suggests that TBI represents a continued target for clinical and resource allocation [32,33]. Increasing TBI in-hospital mortality may also be a result of improved pre-hospital care, but it has been suggested that in-hospital care has trailed the advances made in the triage and transport of TBI patients prior to hospitalization [28,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%